2018
DOI: 10.1002/adma.201705013
|View full text |Cite
|
Sign up to set email alerts
|

Structuring of Hydrogels across Multiple Length Scales for Biomedical Applications

Abstract: The development of new materials for clinical use is limited by an onerous regulatory framework, which means that taking a completely new material into the clinic can make translation economically unfeasible. One way to get around this issue is to structure materials that are already approved by the regulator, such that they exhibit very distinct physical properties and can be used in a broader range of clinical applications. Here, the focus is on the structuring of soft materials at multiple length scales by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 119 publications
(138 reference statements)
1
63
0
Order By: Relevance
“…Biomaterials are widely used to develop active medical devices capable of promoting tissue regeneration and functional restoration . During these processes, the extracellular matrix (ECM) with its complex and dynamic microenvironment plays a pivotal role in regulating cell adhesion, growth and proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials are widely used to develop active medical devices capable of promoting tissue regeneration and functional restoration . During these processes, the extracellular matrix (ECM) with its complex and dynamic microenvironment plays a pivotal role in regulating cell adhesion, growth and proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…Besides enhancing the resolution, a support bath can also provide long‐term stability in a humid environment, limiting the risk of cell damage during the manufacturing process. This paves the way for long or slow prints and the generation of larger, more clinically relevant constructs and helps expanding the window of biofabrication as it enables more cytocompatible processes without sacrificing shape fidelity (Figure A,B) . But the use of support bath also comes with new challenges.…”
Section: Recent Progress For Controlling Shapementioning
confidence: 99%
“…These microgel‐based materials also exhibit rapid self‐healing properties postshearing, allowing the quick trapping of extruded inks. Sheared gels from 0.5 wt% agarose particles have been successfully used as support . The particle size ranged from 2 to 11 µm and formed a weak, reversible network.…”
Section: Recent Progress For Controlling Shapementioning
confidence: 99%
“…Polyacrylic acid (PAA; Figure ) is another synthetic hydrophilic polymer used to create superabsorbent gels for nappies and cosmetics under the commercial name “carbomer.”61 Carbomers are traditionally synthesized in a benzene solvent, raising issues for medical applications. Other solvents, such as ethyl acetate and cyclohexane,62 can be used as an alternative.…”
Section: Topical Ocular Drug Delivery: Eye Dropsmentioning
confidence: 99%
“…Another innovation investigated for overcoming the eye's natural barriers to drug delivery and improving the bioavailability of the carried drug is to increase the viscosity of the eye drop 7a,69b,82. Tests have shown that more viscous drops show a higher resistance to lacrimal clearance and stay resident on the surface of the eye longer 2,10b,38,51,61,76,83. As with mucoadhesion, this increases the window available for drug delivery.…”
Section: Innovations In Topical Ocular Drug Deliverymentioning
confidence: 99%